PENILAIAN PELATIH DAN PENGAWAS PERTANDINGAN TERHADAP KINERJA WASIT PSSI SIDOARJO (PADA PERTADINGAN PLAYOFF KOMPETISI INTERNAL PERSIDA) - ADIEN H, AKHMAD ADIEN (Jurnal Prestasi Olahraga, 2013)
This?t the aim of this research is to know the assesment of coach and supervisor in a competition towards the refree?s working in play off section in internal competition Persida SIDOARJO. The competition is success when the competition process is peaceful and all of teams feels satisfied about the referee?s leadership.. Research results: The performance of the PSSI Sidoarjo's referee during lead's playoffs of Persida internal competition , according to the Coach and supervisor competition, generally categorized as good mark (score 7.03). Keywords: Referee, Performance, Football Competition